2014
DOI: 10.14475/kjhpc.2014.17.3.122
|View full text |Cite
|
Sign up to set email alerts
|

Awareness of Good Death and Attitudes toward Terminal Care among Geriatric Hospital Nurses

Abstract: Purpose:We conducted a descriptive correlational study to determine a relationship between nurses' awareness of good death and attitudes toward terminal care, which in turn could be used as basic data for improvement of the quality of terminal care at geriatric hospitals. Methods: From April 3, 2013 through April 22, 2013, data were collected from 230 nurses working at geriatric hospitals. Results: Nurses' attitudes toward terminal care showed no significant correlation with awareness of good death, but it was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 15 publications
2
6
1
1
Order By: Relevance
“…The majority of nurses (73.1%) were shown to have previously experienced HC education, which is similar to the findings of previous research wherein over two-thirds of nurses working in geriatric hospitals were trained in HC [25]. These results indicate that nurses are fairly well prepared for end-of-life care in care settings for geriatric patients in Korea.…”
Section: Discussionsupporting
confidence: 85%
“…The majority of nurses (73.1%) were shown to have previously experienced HC education, which is similar to the findings of previous research wherein over two-thirds of nurses working in geriatric hospitals were trained in HC [25]. These results indicate that nurses are fairly well prepared for end-of-life care in care settings for geriatric patients in Korea.…”
Section: Discussionsupporting
confidence: 85%
“…Literature reports that married nurses have more social relationships and receive emotional support ( Banakhar, 2017 ). In the studies by An and Lee (2014) and Zaman et al (2021) , it was reported that the marital status of health care workers did not make a significant difference in the perception of a good death, while in the study by Koç et al (2017) , it was reported that single nurses had more positive attitudes toward death than married ones. In the study conducted by Kim and Kim (2021) , it was found that nurses’ perceptions of good death had significant differences by marital status and that married nurses had higher perceptions of good death than single nurses.…”
Section: Discussionmentioning
confidence: 95%
“…Positive perceptions of death reduce fear and anxiety regarding death [11], while negative perceptions of death cause nurses to experience limitations when nursing patients who are in pain and when handling death-avoiding behaviors in patients [12]. Although perceptions of death are considered to be a major factor affecting attitudes towards EOL care, a prior study showed no significant correlation [13], suggesting that this issue should be re-investigated.…”
Section: Importance Of Researchmentioning
confidence: 99%
“…The tool developed by Cho and Kim [22] Frommelt Attitudes toward Nursing Care of the Dying Scale (FATCOD) [23] was used. Cho and Kim [22] developed a Korean version of the tool to be used for research into the attitudes of nursing students, and since then, many researchers have administered it to nurses [13,24], thereby ensuring its validity. This tool is composed of 30 questions, including 20 questions on attitudes towards individual terminal patients and 10 questions on attitudes towards family members.…”
Section: ) Attitudes Towards End-of-life Carementioning
confidence: 99%